2014
DOI: 10.1038/nm.3645
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia areata is driven by cytotoxic T lymphocytes and is reversed by JAK inhibition

Abstract: Alopecia areata (AA) is a common autoimmune disease resulting from damage of the hair follicle by T cells. The immune pathways required for autoreactive T cell activation in AA are not defined limiting clinical development of rational targeted therapies1. Genome-wide association studies (GWAS)2 implicated ligands for the NKG2D receptor (product of the KLRK1 gene) in disease pathogenesis. Here, we show that cytotoxic CD8+NKG2D+ T cells are both necessary and sufficient for the induction of AA in mouse models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
901
1
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 767 publications
(945 citation statements)
references
References 28 publications
27
901
1
16
Order By: Relevance
“…Recently it was shown that systemically administered pharmacological inhibitors of Janus kinase (JAK) family of protein tyrosine kinases, as downstream efectors of the IFN-γ and γc cytokine receptors, prevented the development of alopecia areata in a mouse model reducing the accumulation of efector T cells in the skin [63]. During the course of the study, the authors noticed unexpected regrowth of HFs after topical treatment with JAK-STAT inhibitors.…”
Section: Dermal Papilla Cells and Their Inductive Propertiesmentioning
confidence: 99%
“…Recently it was shown that systemically administered pharmacological inhibitors of Janus kinase (JAK) family of protein tyrosine kinases, as downstream efectors of the IFN-γ and γc cytokine receptors, prevented the development of alopecia areata in a mouse model reducing the accumulation of efector T cells in the skin [63]. During the course of the study, the authors noticed unexpected regrowth of HFs after topical treatment with JAK-STAT inhibitors.…”
Section: Dermal Papilla Cells and Their Inductive Propertiesmentioning
confidence: 99%
“…Transfer of these cytotoxic cells from mice with alopecia areata induced alopecia areata in healthy mice; on the other hand, NKG2D+ T cell-depleted lymph node cells transferred from the diseased mice to the healthy mice did not cause any disease. Interferon produced by NKG2D+ T cell is thought to contribute to the loss of immune-privileged status of hair follicles [11].…”
Section: Pathogenesismentioning
confidence: 99%
“…ey are considered to be involved in various skin disorders [82] including contact dermatitis, psoriasis, gra versus host disease, vitiligo, alopecia areata [86], and drug eruptions [87]. A er being primed by DCs, CD8 T cells circulate around the tissue having assumed a cytotoxic memory phenotype.…”
Section: T Cells T Cells In Their Naive State Rst Encounter Apcs In Smentioning
confidence: 99%